UNTAPPED HORIZONS: POSSIBILITIES FOR TOURISM GROWTH IN UDHAM SINGH NAGAR (UTTARAKHAND) - Sachin Kumar (IJRDO- Journal of Educational Research, 2025)
This study examines the latent tourism potential in the lowland district of Udham Singh Nagar in Uttarakhand in a multidisciplinary perspective based on geography, policy analysis, cultural studies, and comparative benchmarking. Although the region is not seen in the limelight as the Himalayan tourism circuits, this paper illustrates that the region has varied potentials of developing sustainable tourism because of its unique agro-ecological environment, religious heritage sites, Tharu and Kumaoni cultural resources, and transport links. The review applies a systematic approach to the study that entails resource mapping, policy diagnostics, and regional model synthesis in determining the feasible tourism routes comprising of agro-tourism, spiritual circuits, eco-cultural trails, and women-led microenterprises. To coordinate the development with the empowerment of people and the ecological robustness, four implementation pillars are suggested to be addressed, including the district-level tourism planning, skill-building programs, digital heritage integration, and multi-stakeholder governance. The study provides a blueprint that can be replicated by implementing visual data, GIS-mapped figures, and a custom strategic model in expanding tourism in non-traditional geographies. The results highlight the fact that institutional convergence and digital inclusion has the potential of transforming Udham Singh Nagar into one of the most important lowland tourism nodes in the emerging regional tourism paradigm in India.